Actinorhodin Biosynthesis Terminates with an Unprecedented Biaryl Coupling Reaction. (27th December 2022) - Hashimoto, Makoto; Watari, Susumu; Taguchi, Takaaki; Ishikawa, Kazuki; Kumamoto, Takuya; Okamoto, Susumu; Ichinose, Koji
Abstract: A plethora of dimeric natural products exist with diverse chemical structures and biological activities. A major strategy for dimerization is aryl coupling catalyzed by cytochrome P450 or laccase. Actinorhodin (ACT) from Streptomyces coelicolor A3(2) has a dimeric pyranonaphthoquinone structure connected by a C−C bond. In this study, we identified an NmrA‐family dimerizing enzyme, ActVA‐ORF4, and a cofactor‐independent oxidase, ActVA‐ORF3, both involved in the last step of ACT biosynthesis. ActVA‐ORF4 is a unique NAD(P)H‐dependent enzyme that catalyzes the intermolecular C−C bond formation using 8‐hydroxydihydrokalafungin (DHK‐OH) as the sole substrate. On the other hand, ActVA‐ORF3 was found to be a quinone‐forming enzyme that produces the coupling substrate, DHK‐OH and the final product, ACT. Consequently, the functional assignment of all essential enzymes in the biosynthesis of ACT, one of the best‐known model natural products, has been completed. Abstract : The last dimerization step of actinorhodin (ACT) biosynthesis was established through biochemical studies. ActVA‐ORF4 is a unique NAD(P)H‐dependent enzyme that catalyzes the biaryl‐coupling reaction using 8‐hydroxydihydrokalafungin (DHK‐OH) as the sole substrate. ActVA‐ORF3 is a quinone‐forming enzyme that forms DHK‐OH and ACT. The present results complete the functional assignment of essential enzymes for ACT biosynthesis.